Accountability and transparency : a guide for state ownership. (OECD Publishing, 2010)
This guide is meant to facilitate the practical implementation of the OECD Guidelines on Corporate Governance of State-Owned Enterprises in the areas of transparency and accountability. It provides viable policy options and a step-by-step road map on how to address typical difficulties, risks and hurdles that may be encountered It also provides concrete examples of good practices to help governments, their ownership entities and other stakeholders to evaluate existing practices and support reforms.--Publisher's description.